Physiological Traits and Yield Performance of Mungbean (Vigna radiata (L) Wilczek) as Influenced by Light Intensities (Bangladesh Agronomy Journal, 2018)
An experiment was carried out at the Crop Physiology and Ecology Research Field, Hajee Mohammad Danesh Science and Technology University (HSTU), Dinajpur during the period from March to June 2016 to evaluate some physiological traits and yield performance of mungbean variety under different light intensities and to find out potential mungbean variety as intercrop. The experiment was laid out in a split -plot design with three replications. Three light intensities (L100 - full sunlight, L75- 75 % of full sunlight and L50- 50% of full sunlight) were assigned in the main plots and four varieties (BARl Mung-6, Binamoong8, Binamoong5 and BU Mug-4) in the subplots. White and red colour Mosquito nets were used for maintaining 75 and 50 percent of full sunlight. Light percentages of mosquito nets were measured by light meter (21YE35). Mosquito nets of different colors and pore size were used for maintaining 75 and 50 percent of full sunlight. The seed yield of BARI Mung-6 and Binamoong8 performing well in under partial shade condition but the grain yield of Binamoong5 and BU Mug-4 was reduced drastically under partial shade condition. Greater proline accumulation in leaf, higher leaf chlorophyll content, higher pods plant-1, higher seeds pod-1, greater seed size and better seed yield plant-1 under partial shade condition were contributed to better tolerance of BARI Mung-6 and Binamoong8 under low light stress.Bangladesh Agron. J. 2017, 20(2): 67-74